2003
DOI: 10.1159/000074352
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Dmrt1 protein in developing and in sex-reversed gonads of amphibians

Abstract: Many genes are known to be involved in gonadal differentiation in vertebrates. Dmrt1, a gene that encodes a transcription factor with a DM-domain, is considered to be one of the essential genes controlling testicular differentiation in mammals, birds, reptiles, amphibians and fish. However, it still remains unknown which testicular cells of animals other than mice and chicks express Dmrt1 protein. For an explanation of its role(s) in testicular differentiation in vertebrates, the expression of the Dmrt1 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…In E. sinensis, however, Dmrt1 is on a putative autosome, as in humans (Raymond et al, 1999a) and amphibian Rana rugosa (Aoyama et al, 2003), whereas in chicken and birds, it is Z-linked necessary for testis development (Smith et al, 1999(Smith et al, , 2003Raymond et al, 1999b). Moreover, in contrast to the organisms just mentioned, the expression of this gene in E. sinensis begins at J1, whereas gender is already determined at the earlier M (Lee et al, 1994).…”
Section: Discussionmentioning
confidence: 93%
“…In E. sinensis, however, Dmrt1 is on a putative autosome, as in humans (Raymond et al, 1999a) and amphibian Rana rugosa (Aoyama et al, 2003), whereas in chicken and birds, it is Z-linked necessary for testis development (Smith et al, 1999(Smith et al, , 2003Raymond et al, 1999b). Moreover, in contrast to the organisms just mentioned, the expression of this gene in E. sinensis begins at J1, whereas gender is already determined at the earlier M (Lee et al, 1994).…”
Section: Discussionmentioning
confidence: 93%
“…Although the expression of DMRT1 in female gonads were reported in various species including reptiles, fishes, birds and mammals (Aoyama et al, 2003;De Grandi et al, 2000;Kettlewell et al, 2000;Marchand et al, 2000;Raymond et al, 1999), knockout analysis in mice demonstrated that DMRT1 is required for mammalian testis differentiation, and not required for the ovary development . Thanks to the hermaphroditic gonad, the grouper DMRT1 was revealed to be expressed only in the spermatogenic cells, whereas no DMRT1 protein was observed in ovarian tissue and oocytes (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Especially the finding of DMY, a recent duplicate of DMRT1 in teleost Japanese medaka, was identified as sex determination gene for testis development (Matsuda et al, 2002;Zhang, 2004), indicating that DMRT1 may have important roles in testis determination in teleosts. However, some inconsistent DMRT1 expression patterns have been reported from different species (Aoyama et al, 2003;Gao et al, 2005;Guo et al, 2005;Ohmuro-Matsuyama et al, 2003;Pask et al, 2003). In this study, we selected the interest- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many sex-determination genes, including Sry (sex-determination region of chromosome Y), 1) Sox9 (SRY box-containing gene 9), 2) Dmrt1 (Doublesex and mab3-related transcription factor 1) and Dmrt2 (Doublesex and mab3-related transcription factor 2), 3) Foxl2 (forkhead box L2), 4) Rspo1 (R-spondin1), and β-catenin, 5) have been implicated in sexual determination. Dmrt genes have been identified in species such as mammals, 6) birds, 7) amphibians, 8) and teleosts. 9) However, Sry genes have not been identified in non-mammalian vertebrates.…”
Section: De Novo Transcriptome Sequencing To Identify the Sex-determimentioning
confidence: 99%